(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
The article considers the central bank as a system‑forming institution of the state’s monetary system. It reveals the key channels through which the Bank of Russia influences the conditions of money circulation via monetary policy, interest‑rate setting, the safeguarding of financial stability and the integration of sustainable development principles into the regulatory framework. It is shown that the transmission of regulatory decisions is implemented through the banking sector, which provides payment services, safekeeping of funds, credit to the economy and the reallocation of resources in favour of more sustainable projects. The importance of the resilience and security of the financial and banking infrastructure, including technological, operational and ESG‑related risks, is substantiated as a prerequisite for the reliable functioning of monetary circulation. The article concludes that the role of the central bank is of a complex nature, combining monetary, supervisory, infrastructural and coordination functions aimed at maintaining the stability of the national currency and the financial system.